Building surveys - Glover, P. V. (London : Routledge/Taylor & Francis Group, 2013)
'This updated eighth edition features new material on modern methods of construction, and the drive for green homes.Essential reading for building construction students, professional surveyors, and others who may be required to inspect and report on buildings. Illustrated throughout with colour photos showing examples of building defects in full detail.Building Surveys has been a trusted guide for both students and professionals for over 30 years, evolving throughout its eight editions to address the challenges and responsibilities of the building surveying role. It covers everything needed for initial inspections such as equipment, know-how and procedures to writing an accurate report, making it indispensable to those practicing in or studying this field. All the structural aspects of property surveying are explained, covering foundations, walls and roofs as well as what to look out for, and how to deal with problems. Materials and techniques no longer in use are covered as well as new technologies, so the reader is prepared for anything they might encounter. Legal considerations and recent cases are also used to illustrate good working practice, making this an extremely practical companion to the subject.'--
First edition published 1983.
Includes bibliographical references (pages 335-336) and indexes.
Keywords: Building inspection